The Innovative Use of the Relaxation Process in Counseling - Downing, Lester N.; Brigham Young Univ., Provo, UT. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1971)
This paper demonstrates how the proper use of the relaxation process may: (1) make the counseling experience more fruitful and pleasant; (2) facilitate the maximum functioning of the client; (3) reduce physical and emotional tensions; (4) create a physical condition more conducive to attacking other problems; (5) clear the mind for clear and logical thinking; and (6) promote productive and creative efforts by which worthwhile achievements may be realized. The other discusses the goals and possible outcomes of counseling and the place of relaxation in this process. Much of the paper is given over to the principles and actual mechanics involved in relaxation training. Emphasis is on relaxation as a tool for building self-confidence in the client, as well as on behavior changes. A brief consideration of the limitations of the relaxation process concludes the paper. (Author/TL)
ERIC Note: Paper presented at American Personnel and Guidance Association convention, Atlantic City, N. J., April 4-8, 1971.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Anxiety; Behavior; Behavior Change; Behavior Modification; Counseling; Counseling Effectiveness; Counseling Objectives; Counselor Performance; Desensitization; Inhibition; Relaxation Training